Doubly stochastic models for spatio‐temporal covariation of replicated point processes. Issue 1 (19th July 2021) - Gervini, Daniel
Abstract : This article proposes log‐linear models for the latent intensity functions of replicated spatio‐temporal point processes. By simultaneously fitting correlated spatial and temporal Karhunen–Loève expansions, these models produce spatial and temporal components that are usually easy to interpret and capture the main directions of spatio‐temporal correlation. The asymptotic distribution of the estimators is derived, and their finite sample properties are studied by simulation. As an example of application, we analyze the spatio‐temporal patterns of usage of a bike station in the Divvy bike‐sharing system of the city of Chicago. Résumé : Dans cet article, l'auteur utilise des modèles log‐linéaires pour estimer des fonctions d'intensité latente de processus ponctuels spatio‐temporels répliqués. Plus précisément, un ajustement de ces modèles à des développements de Karhunen–Loève corrélées dans l'espace et dans le temps lui permet d'obtenir des composantes spatiales et temporelles qui capturent les principales directions de la corrélation spatio‐temporelle en plus d'être faciles à interpréter. Le comportement à distance finie ou infinie des estimateurs proposés est exploré à travers leur distribution asymptotique et une simulation numérique. En guise d'illustration pratique, l'auteur utilise ces estimateurs pour analyser les données d'utilisation du système de partage de vélos Divvy de la ville de Chicago.